Gauging scholars’ acceptance of Open Access journals by examining the relationship between perceived quality and citation impact - Walters William H. (Journal of Data and Information Science)
For a set of 1,561 Open Access (OA) and non-OA journals in business and economics, this study evaluates the relationships between four citation metrics—five-year Impact Factor (5IF), CiteScore, Article Influence (AI) score, and SCImago Journal Rank (SJR)—and the journal ratings assigned by expert reviewers. We expect that the OA journals will have especially high citation impact relative to their perceived quality (reputation).